Economic Disruption And Fiscal Decentralization: Labor Market Restructuring In East Java - Allen Pranata Putra; Ignatia Martha Hendrati; Kiky Asmara (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study aims to examine how economic disruption reshapes the labor market structure in East Java and to analyze the role of fiscal decentralization in responding to these changes. The study addresses the emerging gap between traditional sectors and technology-based sectors, as well as the need for adaptive regional policies to ensure inclusive and sustainable employment. Methods – This study employed a qualitative approach using in-depth interviews, observation and documentation. Informants were selected through purposive sampling and involving eleven stakeholders from government institutions, the private sector and industry practitioners in East Java. Data were analyzed through data reduction, triangulation and thematic analysis to ensure validity and interpretative depth. Findings – The findings show three specific patterns. First, manufacturing and trade were the sectors most affected by digitalization and automation, as both experienced declining labor absorption, especially for low- and medium-skilled workers. Second, new opportunities emerged in the digital economy, creative industries, and technology-based construction, but these sectors mainly absorbed workers with digital and specialized skills, creating a skills mismatch in the labor market. Third, fiscal decentralization enabled local governments to respond through targeted strategies, particularly digital skills training, support for SME digitalization, and collaboration with the private sector for workforce reskilling. However, unequal fiscal capacity across regions remained a major barrier to balanced labor absorption. Research Implication – This study offers practical implication for policymakers in designing adaptive fiscal strategies that are more responsive to labor market transformation, especially in aligning workforce development with shifting sectoral demands Originality – This study contributes to the literature by linking economic disruption, fiscal decentralization and labor market change within a regional qualitative framework, while highlighting how decentralized fiscal responses shape employment adaptation in a developing regional context.